Dykes and canal system for fruit plantation inlow-land areas of Dakshin Dinajpur (WB) - Islam, Siddikul; Saha, Debraj; Paramanik, Bappa; Goswami, Biswajit; Mandal, Nakul (Indian Horticulture, 2024)
Fruits orchard have the potential to provide higher returns than the conventional agronomic crops due to lower input costs and better tolerance to biotic and abiotic stresses. Maximum cultivated area in the Dakshin Dinajpur District of West Bengal is low-land which is dominantly covered with the traditional cropping system which is very low in economical return. Present intervention targeted to develop a diversity orchard in low-lands by making of dykes and canals for higher economic return. Superior and commercial varieties of different fruit crops were incorporated in the orchard. To achieve sustainable profit, good horticultural practices were followed. Benefit cost ratio was 1.25 after four years of plantation and showed a rapid increase over the next few years, as gross input cost became almost fixed and the gross return kept increasing. Therefore, a diversity orchard developed in low-land area has a great potential to achieve sustainable higher income for common farmers of Dakshin Dinajpur District of West Bengal.